A comparative study of synthetic and semisynthetic approaches for ligating the epidermal growth factor to a bivalent scaffold. (6th November 2017) - Gell, Anna Lena; Groysbeck, Nadja; Becker, Christian F. W.; Conibear, Anne C.
Abstract : A prominent target of monoclonal antibodies as targeted therapies for cancer is the epidermal growth factor receptor, which is overexpressed on the surface of various cancer cell types. Its natural binder, the epidermal growth factor (EGF), is a 53 amino acid polypeptide. Anticancer synthetic targeted immune system engagers (ISErs) comprising two 'binder' peptides, which are attached to a scaffold conveying immune stimulating 'effector' properties, via monodisperse polyethylene glycol chains. So far, preparation of ISErs has been limited to the use of small peptides (8–20 amino acids) as binding functionalities, and they have been entirely synthesized by solid phase peptide synthesis. Here, we describe a synthetic and a semisynthetic approach for the preparation of an ISEr bearing two murine EGF molecules as binding entities (ISEr‐EGF2 ). EGF was either synthesized in segments by solid phase peptide synthesis or expressed recombinantly and ligated to the scaffold by native chemical ligation. We report the successful generation of synthetic and semisynthetic ISEr‐EGF2 as well as several challenges encountered during the synthesis and ligations. We demonstrate the application of native chemical ligation for the design of larger ISEr constructs, facilitating new objectives for the coupling of small binder peptides and larger proteins to multivalent ISEr scaffolds. Copyright © 2017 European Peptide Society and John Wiley & Sons, Ltd. Abstract : Native chemical ligation was used to ligate two molecules of the epidermal growth factor (EGF) to a bivalent polyethylene glycol scaffold. The advantages and disadvantages of synthetic and semisynthetic approaches to generating the EGF thioesters are discussed.